Vehicular impacts on precast concrete bridge piers with grouted sleeve connections. (15th September 2022) - Sun, Wenbiao; Yang, Cancan; Fan, Wei; Wang, Hongxiang; Su, Huaxiang
Highlights: Generated static and impact loading test data to characterize the direct shear damage mechanism for grouted sleeve connections. Proposed and verified a simplified FE modelling method to simulate grouted sleeves subject to a direct shear load. Characterizes the difference in the ability of cast-in-place piers and grouted sleeve connected precast piers to withstand vehicular impacts. Conducted heavy truck-bridge collision analysis to investigate the influence of pier and connection details. Explored feasible retrofit techniques for the precast piers with inadequate impact resistance. Abstract: The grouted sleeve connection has been demonstrated to be robust enough to maintain its integrity under earthquake loads. However, no research to date has examined the connection behaviour under direct shear, resulting in a high risk of failure of the pier subject to a vehicle collision. In this regard, this research first carried out static and impact loading tests on grouted sleeve specimens to characterize their direct shear damage mechanisms. Next, a simplified finite element (FE) modelling method was proposed to simulate connection behaviour, and its accuracy was verified using the test results. Based on the proposed connection modelling approach, truck-bridge collision analysis was performed on a prototype highway bridge that uses grouted sleeves in the pier. From the analysis results, increasing the number of column segments can lead to higher stiffness of the pier when resisting the vehicular impact. The friction property at the connection interface plays an essential role in avoiding unacceptably large rebar shear stress due to excessive sliding and developing the diagonal compression strut to resist the impact load. Finally, feasible retrofit techniques were explored for the precast concrete piers that showed inadequate impact resistance.